THE IMPACTS OF BUSINESS INTELLIGENCE FOR DECISION MAKING - dos Santos, Vitor Luis; Gibertoni, Daniela (Revista Interface Tecnológica, 2022)
The advent of the internet made globalization possible, integrating the world economy through international business, online sales, and the emergence of large corporations, such as Amazon, all these changes led to great competition between companies around the world, generating the need for managers to make assertive decisions more and more quickly, so as not to lose their place in the market. Based on this, several companies decide to implement technological systems that help in these decisions. Among these systems, one can consider implementing the Business Intelligence (BI) methodology, which consists of obtaining, analyzing, sharing, and monitoring information, through tools and techniques that allow putting the methodology into practice, thus obtaining benefits such as reports. and presentations with relevant information that can help managers in the decision-making process. This article, through bibliographical research, aims to analyze what a BI system is, through examples of use cases, it is intended to describe the main advantages of its implementation to increase the competitiveness of companies.